CONCEPTUAL FRAMEWORK FOR ENVIRONMENTAL ACCOUNTING STANDARD - Choy Zevallos, Elsa Esther (2014)
Climate change has become the major concern of this century, is companies that must meet the environmen-tal impacts of production of goods and services. Social information that is involved in scientific knowledge of accounting and lets admit the presence of the emer-gence of a new accounting discipline.The main goal is to identify the most relevant criteria for developing an environmental and a conceptual fra-mework, for which it is based on accounting doctrines developed by researchers. The study has a deductive methodological approach is more qualitative than quantitative and descriptive.The main conclusion states that a predictable and progressive future must be configured from a standard accounting for environmental aspects that serve as re-gistration information, measurement and presentation of the results; well as, make decisions development and clean business practices.